Cosmetic Purchases via Shopee: Brand Image, Price, and Consumer Satisfaction: Pembelian Kosmetika via Shopee: Citra Merek, Harga, dan Kepuasan Konsumen - Karnawati, Tin Agustina (Universitas Muhammadiyah Sidoarjo, 2023)
This research investigates the influence of brand image and price on consumer satisfaction in the context of cosmetic purchasing decisions through the Shopee application. Employing a quantitative approach with a causal research design, a sample of 100 respondents was chosen using purposive sampling. Path analysis was employed to analyze the data with the help of appropriate test instruments. The findings reveal that both brand image and price significantly affect purchasing decisions, which, in turn, impact consumer satisfaction. Surprisingly, while brand image did not directly influence consumer satisfaction, price had a direct effect on it. Furthermore, the study demonstrated that price significantly influences consumer satisfaction through purchasing decisions. The implications of these results provide valuable insights for businesses aiming to understand consumers better and optimize their marketing strategies in the highly dynamic landscape of online shopping. Highlights: Brand image and price both impact purchasing decisions. Price directly affects consumer satisfaction. Price influences consumer satisfaction through purchasing decisions. Keywords: Brand Image, Price, Consumer Satisfaction, Shopee Application, Cosmetic Purchasing